2002
DOI: 10.1074/jbc.m111651200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Human Estrogen Sulfotransferase-PAPS Complex

Abstract: Estrogen sulfotransferase (EST) transfers the sulfate group from 3-phosphoadenosine 5-phosphosulfate (PAPS) to estrogenic steroids. Here we report the crystal structure of human EST (hEST) in the context of the V269E mutant-PAPS complex, which is the first structure containing the active sulfate donor for any sulfotransferase. Superimposing this structure with the crystal structure of hEST in complex with the donor product 3-phosphoadenosine 5-phosphate (PAP) and the acceptor substrate 17␤-estradiol, the terna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
1
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 23 publications
3
70
1
2
Order By: Relevance
“…Superposition of PAPS from the human EST ϩ PAPS structure on to the SULT2B1b active site positions the sulfur atom of PAPS 2.6 Å from the acceptor hydroxyl in line with the acceptor hydroxyl and the bridging oxygen from the leaving group PAP (Fig. 2b) (24). Thus, this geometry supports the in-line displacement mechanism.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Superposition of PAPS from the human EST ϩ PAPS structure on to the SULT2B1b active site positions the sulfur atom of PAPS 2.6 Å from the acceptor hydroxyl in line with the acceptor hydroxyl and the bridging oxygen from the leaving group PAP (Fig. 2b) (24). Thus, this geometry supports the in-line displacement mechanism.…”
Section: Discussionmentioning
confidence: 57%
“…From a previously solved structure of human EST in complex with PAPS, it has been shown that this oxygen is the bridging oxygen between the 5Ј-phosphate and the sulfuryl moiety (Fig. 2b) (24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SULT crystal structures have been determined for mouse estrogen SULT1E1 complexed with PAP/E2 (Protein Data Bank (PDB) codes in parentheses) (1AQU), PAP (1AQY), or PAP/vanadate (1BO6) (14); human estrogen SULT1E1 complexed with PAPS (1HY3) (15); human dopamine SULT1A3 complexed with SO 4 2Ϫ (1CJM) (16) or PAP (10); human hydroxysteroid SULT2A3 complexed with PAP (1EFH) (17); the SULT domain of heparin sulfate-N-deacetylase complexed with PAP (1NST) (18); and human dehydroepiandrosterone sulfotransferase (DEA-SULT) complexed with substrate (1J99) (19). All of these structures incorporate a common PAPS binding region and a variable substrate binding region.…”
mentioning
confidence: 99%